Costs of the police service and mental healthcare pathways experienced by individuals with enduring mental health needs. (February 2017) - Heslin, Margaret; Callaghan, Lynne; Barrett, Barbara; Lea, Susan; Eick, Susan; Morgan, John; Bolt, Mark; Thornicroft, Graham; Rose, Diana; Healey, Andrew; Patel, Anita
Abstract : Background: Substantial policy, communication and operational gaps exist between mental health services and the police for individuals with enduring mental health needs. Aims: To map and cost pathways through mental health and police services, and to model the cost impact of implementing key policy recommendations. Method: Within a case-linkage study, we estimated 1-year individual-level healthcare and policing costs. Using decision modelling, we then estimated the potential impact on costs of three recommended service enhancements: street triage, Mental Health Act assessments for all Section 136 detainees and outreach custody link workers. Results: Under current care, average 1-year mental health and police costs were £10 812 and £4552 per individual respectively ( n = 55). The cost per police incident was £522. Models suggested that each service enhancement would alter per incident costs by between −8% and +6%. Conclusions: Recommended enhancements to care pathways only marginally increase individual-level costs.